Belling the Chinese Dragon at Sea: Western Theories and Asian Realities. (2nd January 2017) - Koo, Min Gyo
ABSTRACT: Against the backdrop of projections of either conflict escalation or legal settlement by Western international relations theories, this article provides a more nuanced and subtle balance between Western theories and Asian realities.